2007
DOI: 10.1258/135763307780096159
|View full text |Cite
|
Sign up to set email alerts
|

Development of a telemedicine protocol for the diagnosis of Alzheimer's disease

Abstract: We developed a telemedicine protocol for diagnosis of Alzheimer's Disease (AD). Assessments by video-conferencing (remote) were compared with face to face (direct) assessments. Eight physicians performed direct assessments and two physicians conducted remote assessments. There was alternate allocation of direct or remote initial assessment. The participants were 20 subjects over 65 years living in a rural area and referred by general practitioners (GPs) because of cognitive impairment. Each assessment included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 16 publications
1
74
1
2
Order By: Relevance
“…In some studies it was reported that patients dropped out because they refused the technical installation and use of telemedical devices. One study including patients with Alzheimer's disease, emphasized the importance of the cooperation of caregiving relatives [71]. These "marginal notes" indicate possible problems of some patients in handling the telemedicine intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies it was reported that patients dropped out because they refused the technical installation and use of telemedical devices. One study including patients with Alzheimer's disease, emphasized the importance of the cooperation of caregiving relatives [71]. These "marginal notes" indicate possible problems of some patients in handling the telemedicine intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies have found agreement between face-to-face (FTF) and telemedicine assessments using the Mini-Mental State Examination (MMSE), Geriatric Depression Scale (GDS), Katz assessment of Activities of Daily Living, Instrumental ADL assessment, and Informant Questionnaire for Cognitive Decline in the Elderly (30, 31). Mild cognitive impairment (MCI) and AD can be diagnosed by telemedicine as studies have found that the accuracy of diagnosis via telemedicine was not inferior to FTF assessment (32, 33).…”
Section: Telemedicine In Dementia Carementioning
confidence: 99%
“…Among adults, remote assessment has been established as reliable and valid for cognitive evaluation of minor cognitive impairment, memory disorders and dementia 19-21 . Remote cognitive assessment of adult-onset dementias by telephone or videoconferencing has been demonstrated to be as accurate as in-person evaluation and correlates well with standard cognitive assessments such as the Mini-Mental Status Exam.…”
Section: Discussionmentioning
confidence: 99%